The Structural Integrity of the Model Lipid Membrane during Induced Lipid Peroxidation: The Role of Flavonols in the Inhibition of Lipid Peroxidation - Sadžak, Anja; Mravljak, Janez; Maltar-Strmečki, Nadica; Arsov, Zoran; Baranović, Goran; Erceg, Ina; Kriechbaum, Manfred; Strasser, Vida; Přibyl, Jan; Šegota, Suzana (Antioxidants (Basel, Switzerland), 2020)
The structural integrity, elasticity, and fluidity of lipid membranes are critical for cellular activities such as communication between cells, exocytosis, and endocytosis. Unsaturated lipids, the main components of biological membranes, are particularly susceptible to the oxidative attack of reactive oxygen species. The peroxidation of unsaturated lipids, in our case 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), induces the structural reorganization of the membrane. We have employed a multi-technique approach to analyze typical properties of lipid bilayers, i.e., roughness, thickness, elasticity, and fluidity. We compared the alteration of the membrane properties upon initiated lipid peroxidation and examined the ability of flavonols, namely quercetin (QUE), myricetin (MCE), and myricitrin (MCI) at different molar fractions, to inhibit this change. Using Mass Spectrometry (MS) and Fourier Transform Infrared Spectroscopy (FTIR), we identified various carbonyl products and examined the extent of the reaction. From Atomic Force Microscopy (AFM), Force Spectroscopy (FS), Small Angle X-Ray Scattering (SAXS), and Electron Paramagnetic Resonance (EPR) experiments, we concluded that the membranes with inserted flavonols exhibit resistance against the structural changes induced by the oxidative attack, which is a finding with multiple biological implications. Our approach reveals the interplay between the flavonol molecular structure and the crucial membrane properties under oxidative attack and provides insight into the pathophysiology of cellular oxidative injury.
Keywords: flavonols; lipid peroxidation; fluidity; myricetin; elasticity; myricitrin; bilayer thickness; quercetin